On the Effects of Transcranial Direct Current Stimulation on Cerebral Glucose Uptake During Walking: A Report of Three Patients With Multiple Sclerosis - Rudroff, Thorsten; Fietsam, Alexandra C.; Deters, Justin R.; Workman, Craig D.; Boles Ponto, Laura L. (Frontiers in Human Neuroscience, 2022)
Common symptoms of multiple sclerosis (MS) include motor impairments of the lower extremities, particularly gait disturbances. Loss of balance and muscle weakness, representing some peripheral effects, have been shown to influence these symptoms, however, the individual role of cortical and subcortical structures in the central nervous system is still to be understood. Assessing [18F]fluorodeoxyglucose (FDG) uptake in the CNS can assess brain activity and is directly associated with regional neuronal activity. One potential modality to increase cortical excitability and improve motor function in patients with MS (PwMS) is transcranial direct current stimulation (tDCS). However, tDCS group outcomes may not mirror individual subject responses, which impedes our knowledge of the pathophysiology and management of diseases like MS. Three PwMS randomly received both 3 mA tDCS and SHAM targeting the motor cortex (M1) that controls the more-affected leg for 20 min on separate days before walking on a treadmill. The radiotracer, FDG, was injected at minute two of the 20 min walk and the subjects underwent a Positron emission tomography (PET) scan immediately after the task. Differences in relative regional metabolism of areas under the tDCS anode and the basal ganglia were calculated and investigated. The results indicated diverse and individualized responses in regions under the anode and consistent increases in some basal ganglia areas (e.g., caudate nucleus). Thus, anodal tDCS targeting the M1 that controls the more-affected leg of PwMS might be capable of affecting remote subcortical regions and modulating the activity (motor, cognitive, and behavioral functions) of the circuitry connected to these regions.